PERSEPSI MAHASISWA AKUNTANSI DAN KARYAWAN DI BIDANG AKUNTANSI TENTANG FRAUD - Putriyani Fransiska Missa; Sarinah Joyce M. Rafael (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
ABSTRACT This study aims to determine the perceptions of accounting students and employees in the accounting sector about fraud, as well as to see the gap between the perceptions of accounting students and the perceptions of employees in accounting about fraud. This type of research is a quantitative study using descriptive statistical analysis methods and the Mann Whitney U-test. The population in this study were accounting students and employees in the accounting sector in Kupang City. Sampling was done by using quota sampling technique and the data were processed as many as 123 samples, namely 74 accounting students and 49 accounting employees. Data collection in this study was carried out by distributing questionnaires to respondents. The results of this study prove that there are no significant differences in perceptions of accounting students' and employees' perceptions of accounting on the fraud and fraud triangle indicators (pressure, opportunity, and rationalization). However, in the illustration of fraudulent behavior, there is a significant difference between the perceptions of accounting students and employees in the accounting field. Although there are differences between the two groups, on the whole accounting students and employees in the accounting sector perceive fraud well. Keywords: Perceptions of Accounting Students, Perceptions of Employees in Accounting,Fraud, Fraud Triangle.